Imaging spectrometry from nature's own atomic lenses - RABALAIS, J. Wayne (Analytical chemistry (Washington), 2001)
Surface atoms are often arranged in patterns with different symmetries or interlayer spacings than the bulk material. Determining these unique structures is important for studying reactive sites in surface catalysis, defining atomic templates for epitaxial film growth, and fabricating well-defined interfaces between different materials.